2021
DOI: 10.3390/ijms222111557
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Degeneration and Microglial Dynamics in Mature Progranulin-Deficient Mice

Abstract: Progranulin (PGRN) is a secreted glycoprotein that regulates numerous cellular processes. The role of PGRN as a regulator of lysosomes has recently received attention. The purpose of this study was to characterize the retinal phenotype in mature PGRN knockout (Grn−/−) mice. The a-wave amplitude of scotopic electroretinogram and outer nuclear thickness were significantly reduced at 6 months of age in Grn−/− mice compared to wild-type (Grn+/+) mice. In Grn−/− mice, retinal microglial cells accumulated on the ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…However, in the current study, transient progranulin knockdown did not affect the expression level of lysosome proteins in RPE cells (Figure 3). Consistent with the results of the current study, the expression of lysosomal proteins in the RPE-choroid complex was not affected in PGRN knockout mouse (34). Lysosomal dysfunction may result from dysregulation of any of the myriad of proteins required for maintaining lysosomal homeostasis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, in the current study, transient progranulin knockdown did not affect the expression level of lysosome proteins in RPE cells (Figure 3). Consistent with the results of the current study, the expression of lysosomal proteins in the RPE-choroid complex was not affected in PGRN knockout mouse (34). Lysosomal dysfunction may result from dysregulation of any of the myriad of proteins required for maintaining lysosomal homeostasis.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, progranulin directly or indirectly binds to trafficking receptors, sortilin, or cation-independent mannose 6-phosphate receptor (CI-M6PR) and is carried to the lysosome (8,30). In the retinal cross section of wild-type mice, high levels of progranulin expression were observed in the RPE layer as well as in the neuronal retina (24,34). However, there was no evidence of the intracellular localization and function of progranulin in RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…CEnC II contributed more as TGF-β sources than the CEnC I cluster, consistent with the scRNA-seq finding that CEnC II expresses more EnMT-related genes. Although the exact nature of the newly discovered Pros, Grn and visfatin signaling pathways in cornea remains unclear, it has been observed that these three signaling pathways were associated with retina, including that Pros1 mutation correlates with inherited retinal degenerations, 58 Grn deficiency results in photoreceptor degeneration in mouse retina 59 and visfatin expression in diabetic rat retina. 60 Although chemerin has been shown to promote vessel growth in the mouse corneal angiogenesis model, 61 its specific role in the cornea remains unexplored.…”
Section: Discussionmentioning
confidence: 99%